2010
DOI: 10.1590/s1679-62252010005000010
|View full text |Cite
|
Sign up to set email alerts
|

Food resources used by three species of fish in the semi-arid region of Brazil

Abstract: Temporary and semi-permanent aquatic habitats in semi-arid Brazil have been reported as important sites supporting a diverse fish fauna. As such, they must be able to trophically sustain fish species that feed at different trophic levels. This study aims to describe the diets of Astyanax aff. bimaculatus, Hoplias malabaricus and Prochilodus brevis in aquatic systems in semiarid Brazil, providing evidence of the importance of these habitats as supporters of large consumers like fish. The diet of the three speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Prochilodus brevis, a specialist detritivore (mud eaters - Silva et al 2010), occurred only in the lower and middle reaches of the basin. Ramos (2012), citing the River Continuum Concept (Vannote et al 1980), suggested the higher occurrence of detritivores, such as those of the genus Prochilodus, should be expected in the lower reaches of the basin, which have a larger amount of accumulated material in the river bottoms.…”
Section: Discussionmentioning
confidence: 99%
“…Prochilodus brevis, a specialist detritivore (mud eaters - Silva et al 2010), occurred only in the lower and middle reaches of the basin. Ramos (2012), citing the River Continuum Concept (Vannote et al 1980), suggested the higher occurrence of detritivores, such as those of the genus Prochilodus, should be expected in the lower reaches of the basin, which have a larger amount of accumulated material in the river bottoms.…”
Section: Discussionmentioning
confidence: 99%
“…The volumetric method has been widely applied in diet studies of medium-small size fishes (e.g. Peterson et al, 2017;Silva et al, 2010) and is considered an efficient and practical way to estimate food item importance (Hyslop, 1980). Prey was identified to the lowest taxonomic level that was feasible based on the degree of decomposition and observable characters.…”
Section: Diet Datamentioning
confidence: 99%
“…In rainforest streams, the physical heterogeneity is characterized by high terrestrial plant cover, canopy, and different types of water flow (pools, rapids, riffles). On the other hand, in semi‐arid streams the aquatic plant cover (e.g., macrophyte banks) allows different types of microhabitats that have a strong influence on the structure of fish assemblages (Gurgel, Silva, Lucas, & Souza, ; Silva, Figueiredo, Ramos, & Medeiros, ). Individual fish may use a high range of physical resources in habitats where their availability is high and, consequently, they may show high ecological variability (Loreau, ).…”
Section: Introductionmentioning
confidence: 99%